A produção da variabilidade e generalização de respostas intraverbais em crianças com TEA - Meletti, Helena Duran (2018)
Rigid and stereotyped patterns of behavior are characteristics observed in people with Autism Spectrum Disorder (ASD) and therefore research on more varied forms of behavior are especially important in guiding people who interact with these individuals. The present study aims to evaluate if a teaching procedure to promote variation of intraverbal responses to social questions of individuals with ASD through progressive Lag from 1 to 4 could promote the generalization of the learned response in the presence of another person in the natural environment and if it is maintained over time. The research participants were four children diagnosed with ASD who received a teaching procedure of six different intraverbal responses through fading out of verbal stimulus and also a teaching procedure of varied responses with progressive Lag from 1 to 4. Stages of tests in structured environment, structured environment with another applicator and in the natural environment occurred before and after the teaching of intraverbal responses, after the teaching of varied answers, and after two weeks of the end of the procedure. The results showed that progressive Lag was effective to promote a varied response to all participants, with variation proportional to Lag requirement (the higher the Lag, the greater the variation). It was also possible to verify that all the participants emitted taught and new answers in the Phase of Teaching of Varied Answers. The generalized analysis data indicate that the varied response occurred in higher structured environment percentage, followed by structured environment with another applicator and appeared in lower percentage in other locations